Digital Islamist Activism and Popular Culture: Propagating Islamism among Indonesian Youth - Ari Ganjar Herdiansah (Studia Islamika, 2026)
While Indonesian scholarship has documented youth hijrah cultures and digital religiosity, less is understood about how Islamist networks adapt ideologically under post-ban HTI. Examining four cases—YukNgaji, Kajian Trotoar, Vespa Moeslim, and Komunitas Literasi Islam—through digital observation (2019–2024), interviews, and narrative analysis, this article shows how Islamists shift from conventional mobilization to engagement through digital popular culture that embeds religious practice within youth activities. Memes and videos attract attention; group rides, study circles, workshops, and charity cultivate sustained participation. What begins as personal spiritual practice—lifestyle changes, hobby communities, study circles—gradually constitutes collective identity with political dimensions. Unlike earlier iterations of pop-Islamism that primarily accommodated consumer modernity, these cases reveal an “ironic appropriation” of digital forms, where subcultural participation and communal solidarity collectively facilitate an ideological formation that feels organic rather than imposed. This adaptive recalibration helps explain how Islamist frameworks continue to circulate within Indonesia’s securitized political landscape.